Jenny Howard Interviewed by Liz Wilson - Howard, Jenny, 1902-1996.; Wilson, Liz. (1982)
Jenny Howard, singer and vaudeville entertainer, talks about her early life in London; World War I; her early involvement and training in the theatre; Percy King; George Formby; her trip to Australia; pantomimes; theatre during the Depression; South Africa and apartheid; World War II and concert parties; Noel Coward; New Guinea; Korea; Japan; New Zealand; Tivoli circuit; Gladys Moncrieff; Gracie Fields; George Wallace; Mo MacKackie; post-War England; USSR and Europe in the 1950s and charity work with the Uncle Bobs.
REEL 3: Sings: Brown slouch hat -- Out of the cold -- Cold snow -- Don't be angry with me, Sergeant -- REEL 4: Sings: Take me back to dear old Blighty.
Recorded at the National Library of Australia, Canberra, between 12 October 1982 and 19 October 1982.
Also available online
Timed summary and uncorrected transcript (typescript, 148 leaves) available.
Keywords: Howard, Jenny, -- 1902-1996 -- Interviews; Women entertainers -- Biography; Women entertainers -- Australia -- Biography; Entertainers -- Biography; Theater -- Great Britain -- History -- 20th century; Theater -- Australia -- History -- 20th century; Australia -- History -- 20th century